Robust model‐free adaptive longitudinal flight control for a flapping wing micro air vehicle with wind disturbances - Yang, Zunyao; Hou, Zhongsheng; Jin, Shangtai (International journal of robust and nonlinear control, 2023)
In this paper, two robust model‐free adaptive control (RMFAC) methods are proposed for a nonlinear flapping wing micro air vehicle (FWMAV) subject to measurable and unmeasurable wind disturbances. Firstly, a novel disturbance‐related full‐form dynamic linearization technique (DFFDL) is developed to transform the FWMAV with measurable disturbances into a dynamic linearization data model. Then, a DFFDL based RMFAC method is designed based on the obtained data model for the FWMAV to suppress the wind disturbances. Next, the stability analysis shows that the system output tracking error converges into a bounded range. And the above result is extended to the case of unmeasurable disturbances. Finally, the simulation comparison results demonstrate the effectiveness of two proposed RMFAC methods.